Decreased vitamin B 12 and folic acid concentrations in acne patients after isotretinoin therapy: A controlled study - Hilal Gökalp; I Bulur; M A Gürer (Wolters Kluwer Medknow Publications, 2014)
Background: Oral isotretinoin treatment might influence the levels of vitamin B 12 and folic acid. Aims and Objectives: The aim of this study is to compare vitamin B 12 and folic acid levels in patients with moderate and severe acne vulgaris with those of the healthy control group and to investigate the effect of isotretinoin treatment on these vitamins. Materials and Methods: Patients who completed 6 months of isotretinoin therapy for moderate and severe forms of acne vulgaris and a control group consisting of healthy individuals between February 2011 and March 2012 were included in the study. Before isotretinoin therapy and at 6.- months of the therapy, serum vitamin B 12 and folic acid levels were measured. In the healthy control group, vitamin B 12 and folic acid levels were assessed only once. Results: In total, 120 patients with moderate and severe acne vulgaris who completed 6 months isotretinoin therapy and 100 healthy individuals who constituted the control group were included in the study. Pre-treatment vitamin B 12 values of the patient group were found to be statistically significantly higher (P = 0.002), but any statistically significant difference was not detected in folic acid measurements (P = 0.566). A statistically significant decrease was detected in post-treatment vitamin B 12 and folic acid levels (P < 0.05). Conclusion: Vitamin B 12 /folic acid treatment should be given under medical surveillance before and during isotretinoin therapy. Supplementation of these vitamins should be recommended in cases of their deficiency, so as to decrease the risks of neuropsychiatric and occlusive vascular diseases.